PEMINDAHAN HAK PAKAI KEPADA PIHAK LAIN DALAM PRESPEKTIF HUKUM ISLAM - Abdul Fattah; Nanda Nabila (MIYAH : Jurnal Studi Islam, 2022)
Abstract: The right of use is the right to use or collect the proceeds from something that is controlled directly by the owner of the goods, and can be transferred to another party with the permission of the owner rather than the goods to be used. In the Perspective of Islamic Law the transfer of the right of use must be with the permission of the owner of the goods that will be the object of the transfer, Imam Abu Hanifah and Ulama Malikiyah and Ulama' others argue that utilizing an item must be with the permission of the owner of the goods, if the owner of the goods does not give permission then the goods that are the object of the transfer of the right of use cannot be transferred to others. This research is a literature study (Library Research), defining literature studies is the result of literature research and the results of thinking conducted by researchers on a study. By collecting a book or reference that can be used as a relevant reference, so as to be able to get a good and correct conclusion. While judging from the type of data information this research includes qualitative research, which is research that cannot be tested with statistics. From the results of research transfer rights to other parties related to renting back rental goods, lending back loans, and renting borrowed goods according to ulma' madzhab Maliki and Madzhab Hambali punish "may" as long as it does not come out of the usefulness of the rented goods, according to imam Shafi'i and Imam Hanafi do not allow renting back before asking permission to the original owner. In the discussion of lending back loans according to Ulama' Madzhab Maliki and Hambali punished "may" as long as it does not come out of expediency, and if it has asked permission will not be allowed then it should not lend back loan goods while according to Ulama' madzhab Shafi'i and Hanafi are not allowed to lend back loan goods unless getting permission from the owner is strengthened in the grace contained in Fathul Qorib. As for the opinions of ulama' Maliki, Hambali, Shafi'i, and Hanafi agreed not to allow renting loans because the rental agreement (Ijarah) is a binding agreement, while the loan agreement is a non-binding voluntary agreement. Keyword: Right of Use, Transfer, Ijarah, Ariyah